2003
DOI: 10.1002/ajhb.10183
|View full text |Cite
|
Sign up to set email alerts
|

Assortative mating by body height and BMI: Finnish Twins and their spouses

Abstract: Assortative mating by body height and weight is well established in various populations, but its causal mechanisms remain poorly understood. We analyzed the effect of phenotypic assortment and social homogamy on spousal correlations for body height and body mass index (BMI, kg/m(2)). Our data derived from a questionnaire administered to the adult Finnish Twin Cohort in 1990 (response rate 77%) yielding results from 922 monozygotic and 1697 dizygotic adult twin pairs who reported information about their body he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 22 publications
10
135
2
1
Order By: Relevance
“…A previous Finnish study, using information on twins and their spouses, found that about half of the spousal correlation in BMI could be attributed to phenotypic assortment and half to social homogamy. 58 However, it is not very probable that phenotypic assortment would have greatly inflated the estimates of common environmental variation in the previous twin studies. If this would be the case, common environmental Genetics of childhood obesity K Silventoinen et al effect should be seen in adult BMI as well, which is, however, rarely the case.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Finnish study, using information on twins and their spouses, found that about half of the spousal correlation in BMI could be attributed to phenotypic assortment and half to social homogamy. 58 However, it is not very probable that phenotypic assortment would have greatly inflated the estimates of common environmental variation in the previous twin studies. If this would be the case, common environmental Genetics of childhood obesity K Silventoinen et al effect should be seen in adult BMI as well, which is, however, rarely the case.…”
Section: Discussionmentioning
confidence: 99%
“…Obese women with an overweight or obese male partner have up to twofold further loss in fertility as compared to their obese counterparts with normal weight partners [8]. A dual loss of fertility is more likely, however, because overweight and obese women tend to marry or cohabit with men of similar weight [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the real world situations of mate advertising (in lonely hearts ads) and actual mate choice, height also appears to matter (Pawlowski & Koziel 2002). Similarly, weight is a factor in both stated preferences and observed choices (Silventoinen et al 2003;Kurzban & Weeden 2005). Despite these relationships having been demonstrated almost entirely in post-industrial societies, they have been used to bolster stories about the evolution of sexual dimorphism (Nettle 2002) and to explain intrasexual competition (Buunk et al 2008) and female character perception (Chu & Geary 2005).…”
Section: Introductionmentioning
confidence: 99%